2014
DOI: 10.1016/j.virol.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 contributes to neutrophil recruitment but not to control of viral replication during acute mouse adenovirus type 1 respiratory infection

Abstract: IL-17-producing CD4+ helper T cells (Th17 cells) promote inflammatory responses to many pathogens. We used mouse adenovirus type 1 (MAV-1) to determine contributions of IL-17 to adenovirus pathogenesis. MAV-1 infection of C57BL/6 mice upregulated lung expression of IL-17 and the Th17-associated factors IL-23 and RORγt. Only CD4+ T cells were associated with virus-specific IL-17 production. Fewer neutrophils were recruited to airways of IL-17−/− mice following MAV-1 infection, but there were no other difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…In the current study, we identified robust induction of IFN-␥ in the heart after MAV-1 infection, consistent with previous studies showing induction of IFN-␥ in MAV-1-infected lungs (25,26). During acute MAV-1 respiratory infection of adult mice, CD4 ϩ and CD8 ϩ T cells are the primary producers of IFN-␥ in the lung (24). IFN-␥ induced during MAV-1 myocarditis is likely produced by infiltrating CD4 ϩ and/or CD8 ϩ T cells, because the robust IFN-␥ induction that we observe correlates closely with recruitment of these cells to the myocardium.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, we identified robust induction of IFN-␥ in the heart after MAV-1 infection, consistent with previous studies showing induction of IFN-␥ in MAV-1-infected lungs (25,26). During acute MAV-1 respiratory infection of adult mice, CD4 ϩ and CD8 ϩ T cells are the primary producers of IFN-␥ in the lung (24). IFN-␥ induced during MAV-1 myocarditis is likely produced by infiltrating CD4 ϩ and/or CD8 ϩ T cells, because the robust IFN-␥ induction that we observe correlates closely with recruitment of these cells to the myocardium.…”
Section: Discussionsupporting
confidence: 92%
“…MAV-1 viral loads were measured in organs and in cardiac myocytes infected ex vivo using quantitative realtime PCR (qPCR) as previously described (24). The primers and probe used to detect a 59-bp region of the MAV-1 E1A gene are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of pThy-derived gd T cells in the dermis was required to increase cellularity near the site of infection and to amplify the overall potency of the immune response, as demonstrated by increased tissue damage in WT and BMpThy mice. Although the complete absence of gd T cells did not translate into increased viral load in this or related systems (52,53), other models showed that mice lacking gd T cells are more susceptible to bacterial infection (54) and have a decreased capacity for wound healing (13). Together, the data indicate that gd T cells are a dynamic population with a range of functions but that they might not respond equally to all inflammatory cues.…”
Section: Cd27mentioning
confidence: 81%
“…CD8 T cells are recruited to the lungs, hearts, and brains of mice infected with MAV-1 (McCarthy et al, 2015a; McCarthy et al, 2015b; McCarthy et al, 2014; Procario et al, 2012; Weinberg et al, 2007). Compared to MAV-1 viral loads in wild type mice, viral loads are higher in brains of MHC class I-deficient mice following i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The strict species specificity of the adenoviruses precludes detailed studies of HAdV pathogenesis in mouse models. We have used mouse adenovirus type 1 (MAV-1) to study the pathogenesis of adenovirus respiratory infection in its natural host (McCarthy et al, 2013; McCarthy et al, 2015b; McCarthy et al, 2014; Procario et al, 2012; Procario et al, 2016; Weinberg et al, 2005). Recently, we used MAV-1 to establish a mouse model of adenovirus myocarditis (McCarthy et al, 2015a) in which intranasal (i.n.)…”
Section: Introductionmentioning
confidence: 99%